Evaluation of Pregnant Woman's Perception of COVID-19 Based on the Health Belief Model in Isfahan - Narges Kalantari; Mohadeseh Khoshgoftar; Fatemeh Moradi; Asiyeh Pirzadeh (Wolters Kluwer Medknow Publications, 2024)
Background: Coronavirus Disease (COVID-19) is a viral disease that has become an international public health concern. Thus, the present study aimed to evaluate pregnant women's perception of COVID-19 based on the health belief model in Isfahan. Materials and Methods: This cross-sectional study includes 100 pregnant women selected by random sampling. Data were collected using an online questionnaire on the Porsline website. This questionnaire examines the knowledge and structures of the health belief model, including perceived susceptibility and severity, perceived barriers and benefits, and self-efficacy regarding the prevention of COVID-19. Data were analyzed using analytical tests such as independent t-test and Pearson's correlation coefficient. The significance level was considered to be <0.05. Results: The results showed that the knowledge of COVID-19 and preventative methods was at a reasonable level among most women (77%). Also, there was a significant correlation between education and self-efficacy. Based on the findings, the mean score of knowledge (F1,99 = 0.116, p = 0.04) and the mean score of perceived susceptibility (F1,99 = 0.02, p < 0.001) of mothers who were pregnant for the first time were significantly higher than mothers who were pregnant for the second time or more. Conclusions: The perceived severity and susceptibility scores were higher than other constructs, indicating women's proper understanding of the risks of COVID-19. However, half of them stated that they do not go to receive services, and this issue can have adverse consequences. The researchers recommend planning to improve other model constructs, such as self-efficacy, for improving women's performance in receiving care.